Pre-infection stages of Austropuccinia psidii in the epidermis of eucalyptus hybrid leaves with different resistance levels - Silva-Souza, Renata Ruiz [UNESP]; da Silva, André Costa; Rodella, Roberto Antônio [UNESP]; Serrão, José Eduardo; Zanuncio, José Cola; Furtado, Edson Luiz [UNESP] (MDPI, 2017)
Rust is a major Eucalyptus spp. disease, which is especially damaging for early-stage plants. The aim of this study was to verify the pre-infection process of Austropuccinia psidii (A. psidii) in the leaves of three phenological stages of Eucalyptus clones with different resistance levels. Plants from the hybrids of Eucalyptus urophylla × Eucalyptus grandis (E. grandis) with variable levels of resistance to this disease were used. The pathogen was inoculated in vitro on abaxial leaf discs of first, third, and fifth leaf stages and maintained under conditions suitable for disease development. Subsequently, samples from these discs were collected 24 and 120 h after inoculation and processed using scanning electron microscopy analysis. No symptoms were seen in any leaf stage of the resistant clone. Additionally, a low incidence of A. psidii germination (1.3-2%) and appressoria (0-0.5%) in three leaf stages was observed. However, the first leaf stage of the susceptible clone presented germination of large numbers of urediniospores (65%) with appressoria (55%) and degradation of the cuticle and wax. From the third stage, the percentage of germinated urediniospores (<15%) and appressoria (<2%) formation of this clone decreased. Protrusions on the leaf surface, associated with the pathogen, were observed on the first and third leaf stages of the resistant clone and on the fifth stage of the susceptible clone, suggesting a possible defensive plant reaction.
Keywords: Eucalypt rust; Leaf discs; Pathogenesis; Phenological stage leaves; Pre-infection stage; Puccinia psidii; Resistance; Scanning electron microscopy